2017
DOI: 10.1016/j.jmii.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological assessment of parvovirus B-19 infection in Egyptian children with sickle cell disease

Abstract: PB-19 infection is detected at high rates among Egyptian children with sickle cell disease and it may result in severe anemia. So, PB-19 must be suspected and screened for in such group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Among 64 haemoglobin SS (sickle cell anaemia) and 36 haemoglobin AS (sickle cell trait) children with IgG positive titers, 24 had evidence of parvovirus B19 DNA as detected by polymerase chain reaction (PCR). 4 Patients with viremia were reported to have a lower baseline haemoglobin than those with a previous history of parvovirus B19 infection denoted by serological markers but no active viremia. 4 Although epidemiology of parvovirus B19 seropositivity in SCD has been well documented, there are few studies that have assessed the presence of persistent DNAemia and if there is an association to RBC transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 64 haemoglobin SS (sickle cell anaemia) and 36 haemoglobin AS (sickle cell trait) children with IgG positive titers, 24 had evidence of parvovirus B19 DNA as detected by polymerase chain reaction (PCR). 4 Patients with viremia were reported to have a lower baseline haemoglobin than those with a previous history of parvovirus B19 infection denoted by serological markers but no active viremia. 4 Although epidemiology of parvovirus B19 seropositivity in SCD has been well documented, there are few studies that have assessed the presence of persistent DNAemia and if there is an association to RBC transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross‐sectional study, Makhlouf et al showed that parvovirus B19 DNAemia appears to be common in SCD. Among 64 haemoglobin SS (sickle cell anaemia) and 36 haemoglobin AS (sickle cell trait) children with IgG positive titers, 24 had evidence of parvovirus B19 DNA as detected by polymerase chain reaction (PCR) . Patients with viremia were reported to have a lower baseline haemoglobin than those with a previous history of parvovirus B19 infection denoted by serological markers but no active viremia …”
Section: Introductionmentioning
confidence: 99%
“…In another study in Egypt, Makhlouf et al assessed the serological and molecular prevalence of the parvovirus B19 in 100 SCD patients and 60 controls. The results revealed that 30% of SCD patients were positive for the parvovirus B19 IgM and DNA, while 24% had positive IgG and DNA by nested-PCR [25].…”
Section: Discussionmentioning
confidence: 97%
“…The virus displays remarkable tropism for human erythroid progenitor cells. In immunocompromised hosts unable to neutralize the antibody, B19 V replicates in erythrocyte precursors e ciently and preferentially, and this infection may persist and lead to pure red cell anemia and other comorbidities [3]. It has been estimated that the peak incidence of infection occurs in children between the ages of 6 and 14 years [4].…”
Section: Discussionmentioning
confidence: 99%